Association between Life’s Essential 8 and depression: a population-based study - Haiying Jin; Ping Wu; Zhenhua Wang; Wei Su; Lili Cai; Haizhi Chen (Archives of Medical Science)
Introduction Previous research has established a connection between depression and an elevated risk of cardiovascular disease. In this study, we sought to examine the association between Life’s Essential 8 (LE8), an updated metric for assessing cardiovascular health, and the prevalence and severity of depressive symptoms.